Control and commitment HR practices, job satisfaction and turnover intentions: a comparison between local and multinational firms in China - Ma, S.; Silva, M.; Callan, V.; Trigo, V. (International Journal of Human Resource Management, 2016)
There is a growing body of literature and debate around control versus commitment human resource management (HRM) systems and their impacts on employees. However, the impacts of these constructs have not been widely examined in more emerging economies. Taking a specific sample of educated professionals working for multinational and local firms in China, this study investigated employee perceptions of control and commitment HR practices, job satisfaction and turnover intentions. A total of 311 respondents completed a structured survey questionnaire. Results revealed that those working for multinational firms reported more positive perceptions of their employers' control and commitment HR practices. In multinational firms, the use of commitment HR practices predicted lower intentions to leave. However, in domestic firms a lack of control HR practices predicted higher turnover intentions. Theoretically, the study adds to discussions about the nature and roles of these constructs, their impacts on HR outcomes and how institutional mechanisms might shape the degree of HRM homogeneity and hybridity across organizations in China. Practically, the study provides guidance to international and local firms on how to improve their HRM effectiveness to achieve a higher retention of their most talented professionals